Correlation between @Infobdg Twitter Account Information Quality with Information Needs Completion - Anindya, Talitha; Damayani, Ninis Agustini; Rodiah, Saleha (Edulib, 2022)
This study discusses the information quality of the @infobdg Twitter account in fulfilling information needs. This study aims to determine whether there is a relationship between the information quality of the @infobdg Twitter account and the fulfillment of followers' information needs in Bandung city. This study adopts the theory of information quality from John Burch and Gary Grudnitski, which consists of 3 pillars: accuracy, timeliness, and relevance. The method used in this study is a quantitative correlational method. The sampling techniques used are simple random sampling techniques. The object of this study is @infobdg Twitter account followers who actively provided comments during the study period from February, 1 2020 – March, 21 2020, and included the residence domicile in Bandung on the user profile. The data collection techniques were derived from the primary data from questionnaires distributed to 82 respondents, and secondary data is literature studies. The analytical methods used are descriptive analysis and inferential analysis. The result of this insulation shows the significant relationship between the information quality of the @infobdg Twitter account, namely accuracy, timeliness, and relevance, by meeting the information needs of followers in Bandung city.